PEMETAAN PENELITIAN PKB DAN BBNKB DI INDONESIA: (STUDI LITERATUR 2022–2025) - Tsaniyeh, Amilatus; Nurdiana, Ilfi; Rahmawati, Sheila; Aini, Nurul; Djasuli, Mohamad (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This research is a literature study that aims to map trends, focus, and research gaps on Motor Vehicle Tax (PKB) and Motor Vehicle Transfer Fee (BBNKB) in Indonesia in the period 2022 to 2025, post-implementation of Law Number 1 of 2022 concerning Financial Relations between the Central and Regional Governments (HKPD Law). Methods: Through searching articles in the SINTA 1 to SINTA 5 databases, 46 selected articles from a total of 107 initial articles were analyzed using the Systematic Literature Review (SLR) approach. Results: The results of the study showed that the majority of studies used quantitative methods (84.78%) and predominantly raised topics around taxpayer compliance, collection effectiveness, and digitalization of services through e-Samsat. The most widely used theories include the theory of planned behavior, attribution theory, and compliance theory, which reflect a behavioral approach to studying tax compliance. In addition, mapping of research locations indicates that areas such as East Java, Bali, and Jambi are the most frequently studied locations. This study provides an important contribution in enriching academic discourse and providing further research directions and input for policymakers in optimizing PKB and BBNKB revenues as sources of Regional Original Income (PAD). Keywords: E-Samsat, tax compliance, PKB and BBNKB